INTERNAL FACTOR ATTRIBUTE IN ISLAMIC BANKS: WHICH ONES CONTRIBUTE TO PROFIT DISTRIBUTION? EVIDENCE FROM MUAMALAT BANK - Bambang Iswanto; Sauci Fisa’i Sabna; Irma Yuliani; Misbahul Munir; Muhammad Nur Faaiz Fathah (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Competition between financial institutions will have a positive and negative impact on the development of a bank. In this case, the existence of Bank Muamalat Indonesia as the first pioneer of banks operating with Sharia principles for 30 years needs to be assessed for its financial performance. This study aims to determine and analyze the effect of the ratio of CAR, ROA, FDR, NPF, and BOPO on Profit Distribution Management at Bank Muamalat Indonesia for the 2014-2021 period. The data used in this study includes data on Bank Muamalat Indonesia's quarterly financial statements from 2014 to 2021. The statistical test method used to analyze data in this study is Multiple Regression Analysis. The results of this study show that the ratio of ROA and FDR has a significant effect on Profit Distribution Management, while the ratio of CAR, NPF, and BOPO does not have a significant effect on Profit Distribution Management. Simultaneously, the ratio of CAR, ROA, FDR, NPF, and BOPO affects Profit Distribution Management. This research has several implications for bank policy regarding the importance of maintaining financial performance ratios and opinions through increasing bank financing disbursements and optimizing Profit Distribution Management.